Stimulation of polygalacturonase production in an immobilized system by Aspergillus sp.: effect of pectin and glucose - Gattas, Edwil Aparecida de Lucca [UNESP]; Bueno, Marcia R. [UNESP]; Ribeiro, Maria H. L. (Springer, 2009)
The synthesis of polygalacturonases (PG) is known to be influenced by Aspergillus growth conditions, namely, environmental factors and pectin content in the cultivation medium containing a mixed carbon source. Optimal conditions were attained at a temperature of 30 A degrees C and an initial pH of 4.5. PG activity (3.29 and 2.48 U/mL) was determined after a two-day culture of Aspergillus sp. HC1 and Aspergillus sp. CC1, respectively, in a basic medium containing 2% citrus pectin as the sole carbon source. The addition of glucose (2% w/v) to the basic medium led to a 2-fold increase in PG production. However, enzyme synthesis was repressed when a higher concentration of glucose was used in the medium containing the mixed carbon source. Spores from the two fungi were immobilized in a 3% Ca-alginate system and the mechanical strength of the gel beads allowed the use of this process system 6-fold longer (288 h) than the free culture. In the Aspergillus sp. CC1 immobilized system, PG production increased nearly 10-fold in the medium with 2% glucose added (5.95 U/mL) in comparison to the medium without sugar (0.55 U/mL). The results demonstrate that a different response in activity was produced by free and entrapped spore systems. PG production remained approximately constant throughout the six 48 h cycles in the medium containing citrus pectin (2% w/v) as the sole carbon source.
Keywords: Polygalacturonase; Aspergillus; Production medium; Immobilization